Indices of Literacy in Preschool Children - Long, Roberta ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1982)
This study was designed to explore how 3-year-olds responded to questions about print, reading, writing, and book knowledge. Nine urban black and eight rural white preschoolers were interviewed and questioned about various literacy concepts. They also completed seven print awareness, reading, writing, and book knowledge tasks. The study found that all of the 3-year-olds were able to identify products and labels from their environment, while nearly 75 percent of the responses identified print as the source of the message. All of the children reported being read to and liking it, although most could not answer why people read. Over half of the children wrote letters or symbol-like forms, and the same number were able to differentiate writing from drawing and recognize their own name. Although the children were able to identify a book and were aware that books are read and have pictures and pages, no child said anything about print, words, or letters in relation to books. Most of the children still identified pictures as the source of stories in books. An appendix provides copies of the seven tasks. (Contains 17 references.) (MDM)
ERIC Note: Paper presented at the Annual Meeting of the Mid-South Educational Research Association (New Orleans, LA, November 10-12, 1982).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Books; Childhood Attitudes; Letters (Alphabet); Literacy; Preschool Children; Preschool Education; Reading; Reading Writing Relationship; Writing (Composition); Print Awareness; Reports, Research; Speeches/Meeting Papers